2017
DOI: 10.14500/aro.10149
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted Synthesis of Some New Curcumin Analogs and Their Corresponding Pyrazoline Derivatives

Abstract: Abstract-In this work, a series of new curcumin mono-carbonyl analogs containing benzyloxy moieties and their pyrazoline derivatives were synthesized using a green method (ultrasound assisted technique) along with traditional method. The work also includes a comparison between the two methods together and with the reported results. Remarkable improvements were achieved by dropping down the reaction time from hours to minutes and obtaining higher yields of the products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…When the same reaction was performed with benzylidene 2 and semicarbazide or thiosemicarbazide in an ethanolic sodium hydroxide (100%), it yielded the dihydropyrazolines 5a and 5b in good yields. It is well known that employing solid NaOH in the reaction condition gives an excellent yield than using NaOH aqueous as a catalyst [38, 39]. The structure of compound 5a was corroborated by spectroscopic data, where its Infrared (IR) spectrum showed bands at 3278, 3204, 1678, and 1587 cm −1 attributed to NH 2 , CO amide, and CN groups, respectively.…”
Section: Resultsmentioning
confidence: 75%
“…When the same reaction was performed with benzylidene 2 and semicarbazide or thiosemicarbazide in an ethanolic sodium hydroxide (100%), it yielded the dihydropyrazolines 5a and 5b in good yields. It is well known that employing solid NaOH in the reaction condition gives an excellent yield than using NaOH aqueous as a catalyst [38, 39]. The structure of compound 5a was corroborated by spectroscopic data, where its Infrared (IR) spectrum showed bands at 3278, 3204, 1678, and 1587 cm −1 attributed to NH 2 , CO amide, and CN groups, respectively.…”
Section: Resultsmentioning
confidence: 75%
“…Senyawa ini disintesis dengan bahan dasar turunan benzaldehida dan keton menggunakan katalis KOH 5% melalui metode refluks dalam waktu 50 menit. (Hawaiz dan Shekh Omer, 2017) menggunakan metode ultrasound untuk mensintesis senyawa analog kurkumin karena lebih efisien, memerlukan waktu yang lebih singkat, tanpa ekstra temperature dan rendemen yang dihasilkan relatif lebih tinggi. Hasil penelitian (Anisa dkk., 2020) juga memperlihatkan bahwa sintesis senyawa analog kurkumin dari 3,4-benzaldehida dan siklopentanon dengan katalis KOH 5% hasilnya lebih efisien, murah, cepat, dengan rendemen yang lebih tinggi sebesar 85,71% menggunakan metode ultrasound dibandingkan dengan metode konvensional.…”
Section: Gambar 1 Struktur Molekul Kurkuminunclassified
“…Previous work reports the efficacy of ultrasonication in enhancing the yield of curcumin and its analogs, suggesting its potential for optimizing EHP synthesis. Studies have reported substantial increases in yield with prolonged ultrasonic extraction times, further underscoring the promise of this method [8,9]. Moreover, the application of ultrasonication in condensation reactions has yielded high yields of curcumin analogs, displaying its versatility and effectiveness in synthetic chemistry [10,11].…”
Section: Introductionmentioning
confidence: 98%